APLIKASI DIGITAL PERANCANGAN APLIKASI DAN IMPLEMENTASI SISTEM REPOSITORI DIGITAL UNTUK PENGELOLAAN KOLEKSI DOKUMEN DI SMK YUPPENTEK 1 TANGERANG : PERANCANGAN APLIKASI - Hasna Fikriyah Ramadhani; Setiawan, Didi; Aji Pangestu, Agung; Haryono, Wasis (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2026)
At SMK YUPPENTEK 1 Tangerang, there are still many issues in managing documents such as student final assignments, scientific papers, and administrative documents. Conventional storage, either physically or scattered across various digital media, increases the risk of losing important data and causes difficulties in searching, monitoring, and sharing information. The SRD was developed using the PHP programming language, built with the Laravel framework and MySQL database, providing a robust and scalable platform. The results of the implementation and functional testing using Black-Box Testing show that the Digital Repository System (SRD) has successfully aided the document digitalization process, storage standardization, and ease of access through access control mechanisms and advanced search features at SMK YUPPENTEG 1 Tangerang, aiming to increase operational productivity and ensure consistent data availability. The main finding of the research is the increased security of digital assets and a reduction in search time of more than 70%. In conclusion, the implementation of the Digital Repository System at SMK YUPPENTEK 1 Tangerang has proven successful as a modern solution that can improve operational efficiency and ensure continuous information availability.